The Effectiveness of Full Day School Management on the Formation of Morals in Elementary Schools: Efektifitas Manajemen Full Day School Terhadap Pembentukan Akhlak di Sekolah Dasar - Dewilyla Lyla; Nur Maslikhatun Nisak (Academia Open, 2021)
This study aims to discuss the application of Fullday School Management at SDIT Nurul Fikri Sidoarjo in the formation of students' morals. The method used in this research is qualitative with a case study approach. Data collection techniques are through interviews, observation, and documentation. The results of this study are the full day school management at SDIT Nurul Fikri in its application has passed several aspects in terms of Human Resources, infrastructure and facilities and the curriculum used by SDIT Nurul Fikri has met the needs of students during the implementation of learning with the Full day school system. Human Resources who are young, energetic, competent and have a high commitment to want to develop, complete and adequate infrastructure and facilities to support the needs and activities of students in this school have successfully implemented the Full day school system in improving school quality. The conclusion of this study is that the implementation of Fullday School management at SDIT Nurul Fikri has been going well and has played a role in the process of forming students' morals.